Gender responsive policy formulation and budgeting in Tanzania: do plans and budgets match? - Ampaire, Edidah L.; Acosta, Mariola; Kigonya, Ritah; Kyomugisha, Sylvia; Muchunguzi, Perez; Jassogne, Laurence T.P. (2016)
The Convention on the Elimination of All Forms of Discrimination against Women has been ratified by more countries than any other UN convention (Gabizon, 2016). The United Republic of Tanzania is one such country that hopes to fully utilize its human resources, both men and women, for socio-economic development. It is recognized that the continued marginalization of women constitutes a major obstacle to rapid socio-economic development of the country (MCDGC, 2005). The United Republic of Tanzania–through the Ministry of Community Development, Gender and Children–has prioritized gender equality through different instruments: the Constitution of the United Republic of Tanzania was amended in 2005 to increase women’s participation in the National Parliament and Local Authorities; the Women and Gender Development Policy of 2000 puts more emphasis on women in development, and the National Strategy for Gender Development was intended to promote gender equality and equity. Despite these developments, challenges still remain, as demonstrated by Tanzania’s low ranking (123rd out of 149 countries) on the 2013 Gender Inequality Index (UNDP, 2015).